Precise Classification, and Accurate Diagnosis: Key Elements for Effective Treatment and Management of Headache Disorders - Otręba, Karina; Czupryńska, Karolina; Czyżniewska, Oliwia; Domański, Mikołaj; Kopczyńska, Barbara; Szałajska, Julia; Wierzejska, Natalia; Wojcieszek, Maria (Journal of Education, Health and Sport, 2024)
Introduction Tension-type headaches (TTH) are a significant health concern that demands precise diagnostic approaches and effective management strategies. A nuanced understanding of their pathophysiology and diagnostic challenges is not just pivotal, but a responsibility we share, for enhancing patient care. Aim This article aims to explore the complex realm of TTH diagnosis and management, underlining the need for precision in diagnostics and the intricate balance of cost-effectiveness. It also delves into the diverse therapeutic options available for treating TTH, presenting a stimulating challenge for healthcare professionals, researchers, and medical students. State of Knowledge Initial diagnosis involves excluding secondary headaches by identifying red flags indicative of serious underlying conditions. A detailed medical history, complemented by patient-recorded pain diaries, enhances diagnostic accuracy. Ancillary procedures like neuroimaging, despite cost-effectiveness debates, are often preferred by clinicians to mitigate diagnostic risks. Validated tools such as the MIDAS and HIT-6 questionnaires provide valuable insights into headache-related disability. Differential diagnosis among headache types relies on recognizing distinctive clinical features. Summary (Conclusions) Effectively managing TTH necessitates a multifaceted approach, incorporating pharmacological, non-pharmacological, and lifestyle interventions tailored to individual patient needs. Collaborative efforts spanning legal, technological, and research domains are crucial for advancing headache diagnostics and therapeutics. While technological advancements offer promise, interdisciplinary collaboration remains fundamental in optimizing patient care outcomes.